A new species of Diadumene (Actiniaria: Diadumenidae) from the subtropical coast of Brazil - Beneti, Julia S.; Stampar, Sergio N. [UNESP]; Maronna, Maximiliano M.; Morandini, Andre Carrara; Da Silveira, Fabio Lang (Magnolia Press, 2015)
Diadumene paranaensis n. sp., collected from the Yacht Club of Paranaguá (Paranaguá Bay, Paraná State, southern Brazil), is described as a new species of sea anemone, based on external and internal morphology, cnidome, and molecular data for 16S/CO3 mitochondrial DNA. This species is partially similar to D. cincta due to the presence of macrobasic pamastigophores in the tentacles, but is distinguished by the cinclides arranged in longitudinal rows and microbasic p-amastigophores in the acontia.
Keywords: Anthozoa; Cnidae; Cnidaria; Sea anemone; South Atlantic; Taxonomy